A rare case of dural arteriovenous fistula presenting as primary intraventricular hemorrhage - Srivastava, Trilochan; Sannegowda, Raghavendra; Sinha, V; Jain, R; Jain, Rahul; Mathur, Tarun (Asian Journal of Neurosurgery, 2017)
Primary intraventricular haemorrhage (PIVH) is rare. Dural arteriovenous fistula causing PIVH is extremely rare. We report a case of a 17 year old boy who presented with left hemiparesis, left lower motor neuron facial palsy and ataxia. His computed tomography head revealed primary intraventricular hemorrhage. Catheter super selective angiography revealed a dural arterio venous fistula with arterial feeder arising from the middle meningeal artery as well as from the inferior marginal tentorial artery. Glue injection led to successful disappearance of the fistula and eventual clinical recovery.
Keywords: Arterio-venous fistula; catheter angiography; cortico-venous reflux; primary intraventricular hemorrhage; venous sinuses